Strategy to Increase Market Reach of Roti Nova MSMEs, Gunung Anyar District, Surabaya Through GoBiz Registration: Strategi Peningkatan Jangkauan Pasar UMKM Roti Nova Kelurahan Gunung Anyar Surabaya Melalui Pendaftaran GoBiz - Alvina Marcelia; Ira Wikartika (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
PKKM Bina Desa is a community service activity carried out by student groups with the aim of solving problems in an area to achieve equitable development. One of the student groups at the East Java